Enterprise Architecture in Poland – the state of present and main directions of evolution - Andrzej Sobczak (Problemy Zarządzania, 2017)
The article aims to present the current implementation of corporate architecture in Polish organizations and to outline possible scenarios for further evolution of this concept. It is based on the analysis of results of the research conducted by its author among companies and public administration units in 2010–2016. The findings provide grounds for concluding that the architectural approach has stagnated after years of dynamic growth in its popularity (ensuing from a considerable increase in awareness of this idea). Many organizations have spotted that the classical mechanisms of corporate architecture management are becoming insufficient in the world of ever faster business changes. It seems therefore necessary to define new approaches to its implementation and application that are better adapted to contemporary challenges.